Contextualizing the Contextual: A Note on the Revolutionary Exegesis of Gregorio L. Aglipay - Smit, Peter-Ben; Vrije (Archīum Ateneo, 2017)
The contextuality of all biblical exegesis is often emphasized—and rightly so. However, the history of contextual exegesis still needs to be written, which leads to a situation in which those involved in “contextual exegesis” are often insufficiently aware of the contextuality of earlier approaches and the fact that they are heirs to a long tradition of contextual biblical interpretation. Using the example of the “revolutionary” exegesis of Gregorio L. Aglipay, this research note illustrates how contextual exegesis may have much earlier roots than is frequently assumed.Keywords: Gregorio Aglipay • Iglesia Filipina Independiente • Contextual Theology • Biblica l interpretation • Jesus • Seven La La st Words